Monitor tecnológico para el estudio del solfeo (2020)
The training of a musician is based on acquiring theoretical and practical skills that are not limited to the domain of a single musical instrument. Singers in particular must develop skills in theory, music reading and music theory that require correct auditory development since this depends on their ability to memorize each sound correctly and also reproduce it accurately at the vocal level. Auditory development has been the focus in musical training [1], traditionally methods implemented to master the solfege consist of interpreting different musical discourses repeatedly to achieve the greatest musical perfection at the vocal level [1]. Solfeggio problem consists of the student's ability to understand, from his perception if he is singing within a frequency range where the heights feel correct and if each note is being started at the right time to give the rhythmic sensation corresponding to the text musical that is being read. Historically, solfege teaching is based on a “teacher-learner” model that allows the student to obtain reliable feedback based on the tutor's experience and knowledge. Callaghan and his team [2] mention the importance of external feedback through visual models that are part of body-kinetic intelligence, which can be used to actively contribute to the development of music theory. In the discussion of this research, similar applications will be explored in detail in order to determine if there are works that carry out an analysis that resembles the one carried out in this project and thus guarantee a commercially viable project. With the framework presented above, this project proposes the development of a technological tool based on engineering tools that, from the area of ​​digital biomedical signal processing, supports students of higher education music programs. The tool would allow students to know and improve their tuning and rhythmic precision through the development of exercises proposed by a professional with a flow focused on learning different skills that present different degrees of difficulty as would be done in the academy. The different audiovisual tools that this research offers to the student will be explored and how a feedback and evaluation in real time is generated that will help them adjust their perception and control of the pitch and their sensation of the musical durations accompanied by the results after the training with the tool.